Twilight reloaded: the peptide experience. Issue 3 (1st March 2017) - Weichenberger, Christian X.; Pozharski, Edwin; Rupp, Bernhard
Abstract : The potential causes of the misinterpretation of peptide density in a significant number of protein–peptide complex structures are analyzed, together with suggestions for good practice and specific education aimed at minimizing overinterpretation and mistakes in protein–peptide complex structure models. Abstract : The de facto commoditization of biomolecular crystallography as a result of almost disruptive instrumentation automation and continuing improvement of software allows any sensibly trained structural biologist to conduct crystallographic studies of biomolecules with reasonably valid outcomes: that is, models based on properly interpreted electron density. Robust validation has led to major mistakes in the protein part of structure models becoming rare, but some depositions of protein–peptide complex structure models, which generally carry significant interest to the scientific community, still contain erroneous models of the bound peptide ligand. Here, the protein small‐molecule ligand validation tool Twilight is updated to include peptide ligands. (i) The primary technical reasons and potential human factors leading to problems in ligand structure models are presented; (ii) a new method used to score peptide‐ligand models is presented; (iii) a few instructive and specific examples, including an electron‐density‐based analysis of peptide‐ligand structures that do not contain any ligands, are discussed in detail; (iv) means to avoid such mistakes and the implications for database integrity are discussed and (v) some suggestions as to how journal editors could help to expunge errors from the Protein Data Bank are provided.